PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, DAN UKURAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2023) - Rihhadatul Auliya; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2025)
Firm value is one of the main indicators that reflects market perception of a company's overall prospects and performance, and serves as a benchmark in determining the attractiveness of the company as an investment. Various factors influence firm value, such as institutional ownership, independent commissioners, and the audit committee. Previous studies have shown mixed results regarding the influence of these factors. This study aims to analyze the effect of institutional ownership, independent commissioners, and audit committee on firm value. The population in this study consists of consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the years 2022–2023. The sample was selected using purposive sampling, resulting in 154 observational data points. The data used are secondary data obtained from the Indonesia Stock Exchange (IDX) and the Bloomberg Laboratory of FEB UNDIP, with documentation as the data collection method. Hypothesis testing was conducted using multiple linear regression analysis with IBM SPSS 29 software. The results of the study show that institutional ownership and audit committee have a significant positive effect on firm value, indicating that a higher number of institutional ownership and audit committee members increases firm value. Conversely, independent commissioners have a significant negative effect on firm value, indicating that a higher number of independent commissioners reduces firm value.